2012
DOI: 10.1299/jamdsm.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis Free Micro EDM in Water Using Electrostatic Induction Feeding Method

Abstract: This paper describes the machining characteristics of electrolysis-free micro EDM in water using the electrostatic induction feeding method. With the electrostatic induction feeding method, if deionized water is used for the working liquid, electrolysis can be prevented because bipolar voltage is applied to the working gap. Results of micro-holes drilling showed that the material removal rate with deionized water is higher than that with oil, and the oversize of holes machined in deionized water is smaller. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…T, and M. Kunieda. [4] developed a electrolysis free micro-EDM method by connecting a pulse power supply and a RC-circle in series. Though many researches have been carried out, little research was done about the ringing effect.…”
Section: Introductionmentioning
confidence: 99%
“…T, and M. Kunieda. [4] developed a electrolysis free micro-EDM method by connecting a pulse power supply and a RC-circle in series. Though many researches have been carried out, little research was done about the ringing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, neither localized discharge nor abnormal arc occurs easily despite the high duty cycle. Experimental results showed that higher material removal rate and more uniform discharge energy can be obtained in the electrostatic induction feeding method compared to the conventional relaxation pulse generator [6]. By theoretical analysis and experimental investigations, the influence of the stray capacitance in the circuit on the discharge energy has been examined [7].…”
Section: Introductionmentioning
confidence: 99%